2010
DOI: 10.1519/jsc.0b013e3181c509f4
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Analysis of Hamstring and Quadriceps Muscle Activation During Jump Landings and Cutting

Abstract: This study evaluated gender differences in the magnitude and timing of hamstring and quadriceps activation during activities that are believed to cause anterior cruciate ligament (ACL) injuries. Twelve men (age = 21.0 ± 1.2 years; body mass = 81.61 ± 13.3 kg; and jump height = 57.61 ± 10.15 cm) and 12 women (age = 19.91 ± 0.9 years; body mass = 64.36 ± 6.14 kg; and jump height = 43.28 ± 7.5 cm) performed 3 repetitions each of the drop jump (jump) normalized to the subject's vertical jump height, and a sprint a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 29 publications
5
44
0
2
Order By: Relevance
“…Strategies to optimize extrinsic factors, such as strengthening the hamstring and quadriceps [1,2], or improving neuromuscular control and proprioception [10,25], demonstrated little effect at reducing overall failure rates. Techniques to manage intrinsic features, such as notchplasty and tibial slope reduction, proved more successful, but are rarely performed due to technical challenges and lack of published outcomes [12,14,38].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to optimize extrinsic factors, such as strengthening the hamstring and quadriceps [1,2], or improving neuromuscular control and proprioception [10,25], demonstrated little effect at reducing overall failure rates. Techniques to manage intrinsic features, such as notchplasty and tibial slope reduction, proved more successful, but are rarely performed due to technical challenges and lack of published outcomes [12,14,38].…”
Section: Introductionmentioning
confidence: 99%
“…15 Conversely, optimizing hamstrings muscle activity and quadriceps-hamstrings cocontraction may stabilize the tibia, resulting in decreased anterior shear and ACL strain. 6,16 Muscle activity proximal to the knee joint may influence knee-motion control. 13,17À19 Weakness and poor control of the hip abductors and external rotators reduce pelvic stability, which may lead to excessive dynamic knee valgus.…”
mentioning
confidence: 99%
“…A number of previous studies have reported that female volleyball players performed better in all tests and were more resistant to fatigue than non-jumper subjects 34,38) . Furthermore, volleyball players showed reduced co-activation of knee flexor/extensor muscles 30,36) . Our results suggest a neural adaptation of the motor control scheme to training 18) , because the demand imposed on the knee joint through the practice resulted in specific muscle adaptations that may have generated strength imbalances in static and dynamic actions acting on this joint 35) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed by previous studies that neuromuscular training results in a reduction in knee ligament injuries, possibly because of biomechanical (decreased landing forces and adduction-abduction moments) and physiological effects (decreased estrogen levels and increased H:Q strength ratios) 11,17) . There is some controversy in the literature about the ability of the isokinetic test as a good predictor of sports performance, since several studies found no relationship between the isokinetic variables of the knee joint and the height reached by subjects in vertical jumping 30,31) . Nevertheless, isokinetic tests have been widely used in a great number of previous studies, as they supply objective, reliable, and reproducible values related to the muscle function of several joints 32,33) .…”
Section: Discussionmentioning
confidence: 99%